Country Partnership Framework for India for the Period FY18-FY22 - World Bank Group (World Bank, Washington, DC, 2018)
India is in a period of unprecedented opportunity, challenge, and ambition in its development, requiring the World Bank Group (WBG) to reposition its partnership with the country. This Country Partnership Framework (CPF), the first since the country’s graduation from IDA to IBRD is being formulated to respond to this challenging context of a dynamic and increasingly global India. It charts a path for how the World Bank, IFC and MIGA will leverage their relative strengths and value propositions to answer the call of today’s India to deliver stronger development outcomes, nationally and globally. In this context, the WBG’s Systematic Country Diagnostic (SCD) distills three key priorities for maintaining the country’s trajectory of poverty reduction and high growth. This CPF is defined by a prioritization of ‘what’ substantive areas the WBG will focus on and an articulation of ‘how’ the Group will engage with India. The CPF posits three focus areas for WBG’s engagement. These are (i) promoting resource-efficient growth; (ii) enhancing competitiveness and enabling job creation; and (iii) investing in human capital.